Storage of Brazilian Cattleya seeds from diverse biomes: lipid composition and effects on germination - Hengling, Mariane M.; Gianeti, Thiago M. R. [UNESP]; Hosomi, Silvério T.; Machado-Neto, Nelson B.; Custódio, Ceci C. (Springer Nature, 2020)
The establishment of seed banks is essential for the conservation of cultivated and wild plant species. Cattleya species are economically important, but many of them are at risk of extinction. In this study, we aimed to evaluate the effects of storage temperature on the physiological quality of seeds of seven congeneric species of diverse biomes from the UNOESTE-OSSSU seed bank and the lipid composition. Seeds were split into sub samples, pre-conditioned to 0.03 g H2O g DW−1 for a week over a supersaturated solution of lithium chloride at 23 ± 2 °C and maintained in rubber-sealed vessels for nine months under four storage temperatures: room temperature (23 ± 2 °C), 5 °C, –18 °C and –196 °C. Germination, the germination speed index, and viability based on a tetrazolium test were evaluated at three-month intervals. Lipid profiles were determined by GC-MS in the original seed lots. Different lipid profiles were found among species. Orchid seeds with a low water content could be stored for a short period in all conditions studied and were considered orthodox short-lived seeds. Cattleya rupestris seeds were more tolerant than the congeners to deterioration under all the storage conditions.
Keywords: Cattleya; Germination; Orchidaceae; tetrazolium; vigour